2008
DOI: 10.1590/s1415-43662008000300005
|View full text |Cite
|
Sign up to set email alerts
|

Mudanças na fertilidade de um Neossolo Regolítico após seis anos de adubação orgânica

Abstract: Visou-se, com o presente estudo, avaliar os efeitos de seis anos de adubação orgânica sobre as características químicas de um Neossolo Regolítico cultivado com batata. Os tratamentos de adubação orgânica foram: 1) esterco (15 t ha-1); 2) cultivo e incorporação da Crotalaria juncea L.; 3) combinação de metade da dose de esterco (7,5 t ha-1) com o cultivo e incorporação da Crotalaria juncea L. e 4) testemunha, sem fertilização. Os ensaios de adubação orgânica e cultivo da batata foram realizados no período de 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
14

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 17 publications
(14 reference statements)
1
15
0
14
Order By: Relevance
“…For OC (Figures 1F-C1, 1F-C2 and 1F-C3), neem cake application increased the variability and the contents in the soil, showing narrower lines at the end of the study. Menezes & Silva (2008) reported similar behavior to the effects of organic fertilizers on soil fertility.…”
Section: Resultsmentioning
confidence: 57%
“…For OC (Figures 1F-C1, 1F-C2 and 1F-C3), neem cake application increased the variability and the contents in the soil, showing narrower lines at the end of the study. Menezes & Silva (2008) reported similar behavior to the effects of organic fertilizers on soil fertility.…”
Section: Resultsmentioning
confidence: 57%
“…As the N/P ratio of manure is generally lower than the N/P ratio of plant uptake, applications exceed the crop needs, resulting in soil P accumulation P and potential loss. Data regarding this undesirable effect in low input family agriculture in the semi-arid region of Brazil have recently been published (Galvão et al, 2008;Menezes & Oliveira, 2008). Data on P accumulation (Sharpley et al, 2004) and P losses through leaching (Koopmans et al, 2007) related to animal manure applications have also been reported in other countries (Siddique & Robinson, 2004;Anderson & Magdoff, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…) No Nordeste do Brasil, especialmente na região semiárida, os solos se caracterizam por apresentar baixa fertilidade natural (Menezes & Oliveira, 2008), e baixa disponibilidade hídrica para o cultivo agrícola, devido principalmente a chuvas torrenciais, que não favorecem a infiltração de água no solo para que haja posterior uso pelas culturas. O cultivo do milho, cultura muito comum na região, necessita de 400 a 600 mm durante o seu ciclo (FANCELLI, 2001), contudo a produção quase sempre é comprometida devido a irregularidade das chuvas.…”
Section: Introductionunclassified